ANALISIS NILAI TAMBAH (VALUE ADDED) PENGOLAHAN SIRUP KAYUMANIS DI KABUPATEN KERINCI PROPINSI JAMBI - Iskandar, Sutarmo; Mulyana, Andi; Yamin, M.; Marwa, Taufik; Nurvalentini, Nurvalentini (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2013)
Abstract The purpose of this study were: (1) to determine how much value added  and profit of cinnamon syrup procsesing in Siulak Deras Mudik Village Gunung Kerinci District Kerinci Regency Jambi Province, (2) to determine the background factors of agroindustry cinnamon syrup in Siulak Deras Mudik Village Gunung Kerinci District Kerinci Regency Jambi Province, and (3) to determine what were the constraints in cinnamon syrup business. This research has been conducted in Producer of cinnamon syrup home industry in Siulak Deras Mudik Village Gunung Kerinci District Kerinci Regency Jambi Province. The location of this research has been taken  as in purposive sampling by considering this area was just one of the cinnamon syrup processing area in Indonesia. The time of this research has been conducted in December 2011 to February 2012.            The results of this study were (1) the value added from cinnamon bark processing into cinnamon syrup Rp. 4,083.33 per once processing with production as much as 48 litres (160 bottles). Selling price per bottle was Rp.16,666.00 and profit was obtained for Rp.9,583.00 per litre production processing, (2) the background factors of the processing of cinnamon syrup was the potential number of cinnamon bark in Kerinci Regency, syrup processing can create added value, and reduce unemployment, and (3) the constraint in the processing of cinnamon bark to cinnamon syrup was capital in cinnamon syrup processing.